Measuring Physical Fitness among Secondary School Students of ages between 10 to 15 Years - Masood Mafooz, a Muhammad Tahir Nazeer, Qasid Naveed, Muhammad Badar Habib2, Badar Mohy ud Din, Muhammad Zia ul Haq, (Opción, 1970)
Physical inactivity globally problem whereby alarge number of the population do not take part in the sports andphysical activity in order to increase health benefits. Sedentarybehavior is a primary risk factor among children. The main purpose ofthe study was to measure the norm of physical efficiency test amongstudents aged 10 to 15 years. Methods: The total of 506 studentsparticipated in the study aged between 10 to 15 Years. They wereregularly participating in physical activity and sports in their dailyroutine life. The norms of physical efficiency test were used forcollecting data from the male students. The age, endurance, speed,muscular strength, explosive strength, and agility of all subjects weremeasured. Results: On the base of analysis of the study the strength ofstudents ages between of 10-15 years were almost half of the studentsstanding broad jump range was between 5-6 feet while almost onethirdof the students were range between 4-5 feet. Conclusion: Thisstudy expressed that the norms of the physical efficiency test is validand reliable to assess the level of fitness among the students. Futureresearch can use these instruments for measuring the level of fitnessamong the participants.